The Implementation of TPACK (Technology, Pedagogy, and Content Knowledge) Framework on Indonesian Online Mathematics Teachers Training - Rohmitawati Rohmitawati (Southeast Asian Mathematics Education Journal, 2018)
This study aimed to describe how the implementation of the TPACK (Technology, Pedagogy, and Content Knowledge) framework used for online mathematics teacher training, and to observe participants’ response of the course. This research was a case study of online training for 30 Indonesian junior secondary school mathematics teachers on a quadrilateral course developed using the TPACK framework. The TPACK framework provides a map for understanding how to effectively integrate technology and instructional strategies into the content. The finding of this study for the teachers in the sample were: (1) The TPACK framework was implemented interactively in the integration process of GeoGebra (technology) using discovery learning strategies (pedagogy) on the square area formula (content) for quadrilateral properties; (2) The use of the TPACK framework on the online course received positive responses from teachers in the sample and they stated that it would be interesting and helpful when used in the classroom.